A study of teak wood quality from community forests in Gunungkidul IV. Mechanical Properties - Sri Nugroho Marsoem; Vendy Eko Prasetyo; Joko Sulistyo; Sudaryono Sudaryono; Ganis Lukmandaru (Jurnal Ilmu Kehutanan)
Mechanical properties of sawn timber are the most important characteristics in many applications, particularly for structural timber. The previous paper in this series reported on the physical properties of teak trees at different sites (Panggang, Playen, Nglipar) from community forests in Gunungkidul regency. In this study, the mechanical properties were evaluated according to British Standards 373:57. The results showed that the timber were classified in the II-III of strength class. By analysis of variance, site factor affected the values of modulus of rupture (MoR) in statical bending strength, maximum compression perpendicular to grain strength, shear strength and hardness. In general, except for MoR, the wood samples from Nglipar gave higher strength levels. Except for cleavage strength, the effects of the axial and radial position of the tree on mechanical properties were mostly negligible. Although linearly related, only modest correlations were observed between the mechanical parameters (MoR/shear strength) and basic density. No significant correlation was found between the values of basic density and modulus of elasticity of static bending strength as well as between basic density and the strength of maximum compression parallel to grain.